Are women breaking the glass ceiling? A gendered analysis of the duration of sick leave in Spain - Ángel L. Martín-Román; Alfonso Moral; Sara Pinillos-Franco (Global Labor Organization (GLO), 2022)
We study the gender gap in the duration of sick leave in Spain by splitting this duration into two types of days - those which are related to biological characteristics and those derived from behavioral reasons. Using the Statistics of Accidents at Work for 2011-2019, we found that women presented longer standard durations (i.e., purely attached to physiological reasons) compared to men. However, when estimating individuals' efficiency as the ratio between actual and standard durations, we found that women were more inefficient at lower levels of income, whereas in case of men, this occurred at higher levels of income. These results were reinforced when considering that men and women do not recover from the same injury at the same rate. Women were more efficient than men across all the compensation distribution, especially at higher income levels.
Keywords: I12; I13; I18; J28; 330; Moral hazard; Glass ceiling; Workplace injuries; Gender; Stochastic frontiers